2022
DOI: 10.53730/ijhs.v6ns1.7092
|View full text |Cite
|
Sign up to set email alerts
|

review on consumer’s attitude & purchase behavioral intention towards green food products

Abstract: Due to ecological concerns, green products have gained more consideration in recent years, & their accessibility is rising. In addition, the presence of an eco-label encourages people to purchase environmentally friendly products. This paper focus to ascertain customer attitudes regarding green food products and compile data on the subject. This study serves as the foundation for the literature review of this research study. This research focuses on green marketing, more precisely on customers' attitude &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…"Behavioral beliefs and attitudes" refer to how favorable or unfavorable a person perceives a behavior (Rustagi & Prakash, 2022). In other words, an attitude is an expression of liking or disliking something.…”
Section: Consumer Attitude and Green Purchase Intentionmentioning
confidence: 99%
“…"Behavioral beliefs and attitudes" refer to how favorable or unfavorable a person perceives a behavior (Rustagi & Prakash, 2022). In other words, an attitude is an expression of liking or disliking something.…”
Section: Consumer Attitude and Green Purchase Intentionmentioning
confidence: 99%
“…The rational behavior theory plays an important role in explaining individual attitudes and their influencing factors (Shi et al, 2021). Past studies have found that attitudes are the most significant motivators of purchase intention for organic cotton clothing (Hasan et al, 2022), upcycled fashion products (Yoo et al, 2021), green hotels (Wang, 2022), and green foods (Rustagi and Prakash, 2022).…”
Section: Attitudes Toward Organic Food Productsmentioning
confidence: 99%
“…Consumer purchasing patterns, on the other hand, can vary substantially. For a long time, corporations and academics have been investigating consumer purchasing behavior (Rustagi & Prakash, 2022), but the intricacy of the buying process has made it extremely difficult to predict and manage trends (Nam, Dutt, Chathoth, & Khan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%